The investigation on employee wellbeing among 2017-2021 KAZGUU ISE alumni - Arsakay, A. (International School of Economics KAZGUU, Nur-Sultan, 2022)
Employee wellbeing is creating an environment, where people can work on full capacity with the help of support, engagement and through positive emotions. This research aims to investigate KAZGUU ISE alumni wellbeing as an employee. It states that KAZGUU alumni are satisfied with work and experiences employee wellbeing. Workplace wellbeing increases employee engagement, decreases “sick leave”, and improves productivity (Westfield Health, 2021). In reality, does employee wellbeing forms employee engagement, decreases “sick leave” and increases productivity or it is a “trendy” phenomena after pandemic? This paper mainly have used Gallup’s, Deloitte’s studies between 2017-2022 years on employee wellbeing. The relevant examples, figures and tables are introduced in the Literature review section. The practical section shares the result of 102 respondents and interview result of five participants. Overall, the results showed that KAZGUU alumni are satisfied with their work and experiences employee wellbeing due to their financial wellbeing. Research have demonstrated that employee wellbeing develops employee brand, increase financial efficiency and improve employer reputation in the labor market
Keywords: KAZGUU ISE alumni